Microbial Communities in Methane- and Short Chain Alkane-Rich Hydrothermal Sediments of Guaymas Basin - Dowell, Frederick; Cardman, Zena; Dasarathy, Srishti; Kellermann, Matthias Y.; Lipp, Julius S.; Ruff, S. Emil; Biddle, Jennifer F.; McKay, Luke J.; MacGregor, Barbara J.; Lloyd, Karen G.; Albert, Daniel B.; Mendlovitz, Howard; et al. (Frontiers in Microbiology, 2016)
The hydrothermal sediments of Guaymas Basin, an active spreading center in the Gulf of California (Mexico), are rich in porewater methane, short-chain alkanes, sulfate and sulfide, and provide a model system to explore habitat preferences of microorganisms, including sulfate-dependent, methane- and short chain alkane-oxidizing microbial communities. In this study, sediments (above 60˚C) covered with sulfur-oxidizing microbial mats surrounding a hydrothermal mound (termed “Mat Mound”) were characterized by porewater geochemistry of methane, C2-C6 short-chain alkanes, sulfate, sulfide, sulfate reduction rate measurements, in-situ temperature gradients, bacterial and archaeal 16S rRNA gene clone libraries and V6 tag pyrosequencing. The most abundantly detected groups in the Mat mound sediments include anaerobic methane-oxidizing archaea of the ANME-1 lineage and its sister clade ANME-1Guaymas, the uncultured bacterial groups SEEP-SRB2 within the Deltaproteobacteria and the separately branching HotSeep-1 Group; these uncultured bacteria are candidates for sulfate-reducing alkane oxidation and for sulfate-reducing syntrophy with ANME archaea. The archaeal dataset indicates distinct habitat preferences for ANME-1, ANME-1-Guaymas and ANME-2 archaea in Guaymas Basin hydrothermal sediments. The bacterial groups SEEP-SRB2 and HotSeep-1 co-occur with ANME-1 and ANME-1Guaymas in hydrothermally active sediments underneath microbial mats in Guaymas Basin. We propose the working hypothesis that this mixed bacterial and archaeal community catalyzes the oxidation of both methane and short-chain alkanes, and constitutes a microbial community signature that is characteristic for hydrothermal and/or cold seep sediments containing both substrates.